Temperlenmiş beynitik bir çeliğin balistik davranışı - (:unkn) unknown (My University, 2010)
Bu çalışmada, temperlenmiş beynitik bir çeliğin 7,62 mm kalibre bir zırh delici ile olan etkileşimi sonrasında meydana gelen hasar incelenmiştir. Mermi çarpma hızı 840 m/s olup atış sıfır derecelik bir açıda gerçekleştirilmiştir. Atış sonrası oluşan delinme yöresinden alınan numune üzerinde mikroyapısal ve fraktografik incelemeler yapılmıştır. Dağlanmış numunede, penetrasyon doğrultusuna yakın yörelerde orijinal mikroyapı morfolojisinin değiştiği ve kaymâ/adyabatik kayma bantlarının oluştuğu gözlenmiştir. Çeliğin delinme modu ise tipik bir taçyaprağı şeklinde açılmadır.

In this study, failure occured after the interaction between an armor piercing 7.62 mm caliber projectile and a tempered bainitic steel was investigated. The shot was performed at zero degree with a projectile velocity of 840 m/s. After the shot, microstructural and fractographical examinations were carried out on the sample, taken from the perforated region. In the etched sample, it is observed that the morphology of the original microstructure has changed and shear/adiabatic shear bands formed in regions close to the direction of penetration. The perforation mode of the steel is a typical petalling.
Ballistic behaviour of a tempered bainitic steel
Keywords: Savunma Bilimleri